A Pemantauan Kadar Obat Dalam Darah Bedaquilin dan Linezolid Pada Pasien Tuberculosis Resistensi Obat : Literatur Review - Ai Yeni Herlinawati Yeni; Santi Purnasari; Retnosari Andrajati; Raden Rara Diah Handayani (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Tuberculosis remains a leading cause of global mortality and morbidity. Current TB elimination programs have not yet met their targets. Drug resistance poses a significant challenge, necessitating effective alternative treatments for drug-resistant TB patients. Bedaquiline and Linezolid are primary drugs (Category A) used to combat drug-resistant TB. However, they come with side effects and toxicity, have narrow therapeutic window, and exhibit pharmacokinetic variability. Therefore, therapeutic drug monitoring (TDM) is recommended to achieve desired treatment outcomes and prevent or minimize potential side effects or toxicity. The objective of this study is to assess the urgency of TDM implementation to address these issues. This research is a literature review involving the synthesis of data from six studies that met inclusion and exclusion criteria. Data sources include Science Direct, PubMed, and Nature. The results indicate that Bedaquiline and Linezolid exhibit pharmacokinetic variability and the occurrence of side effects. Therefore, TDM is recommended for Bedaquiline and Linezolid to achieve desired therapeutic effects and avoid the onset of side effects or toxicity